Lipoxygenase functions in 1O2 production during root responses to osmotic stress. Issue 4 (28th January 2021) - Chen, Tomer; Cohen, Dekel; Itkin, Maxim; Malitsky, Sergey; Fluhr, Robert
Abstract: Drought induces osmotic stress in roots, a condition simulated by the application of high-molecular-weight polyethylene glycol. Osmotic stress results in the reduction of Arabidopsis thaliana root growth and production of 1 O2 from an unknown non-photosynthetic source. Reduced root growth can be alleviated by application of the 1 O2 scavenger histidine (HIS). Here, we examined the possibility that 1 O2 production involves Russell reactions occurring among the enzymatic products of lipoxygenases (LOXs), the fatty acid hydroperoxides. LOX activity was measured for purified soybean ( Glycine max ) LOX1 and in crude Arabidopsis root extracts using linoleic acid as substrate. Formation of the 13(S)-Hydroperoxy-9(Z), 11(E)-octadecadienoic acid product was inhibited by salicylhdroxamic acid, which is a LOX inhibitor, but not by HIS, whereas 1 O2 production was inhibited by both. D2 O, which specifically extends the half-life of 1 O2, augmented the LOX-dependent generation of 1 O2, as expected from a Russell-type reaction. The addition of linoleic acid to roots stimulated 1 O2 production and inhibited growth, suggesting that the availability of LOX substrate is a rate-limiting step. Indeed, water stress rapidly increased linoleic and linolenic acids by 2.5-fold in roots. Mutants with root-specific microRNA repression of LOXs showed downregulation of LOX protein and activity. The lines with downregulated LOX displayed significantly less 1 O2 formation, improved root growth in osmotic stress, and an altered transcriptome response compared with wild type. The results show that LOXs can serve as an enzymatic source of "dark" 1 O2 during osmotic stress and demonstrate a role for 1 O2 in defining the physiological response. Abstract : Light-independent production of singlet oxygen by lipoxygenase occurs in Arabidopsis roots during osmotic stress.